2017
DOI: 10.1002/anie.201705500
|View full text |Cite
|
Sign up to set email alerts
|

Palladium‐Catalyzed Asymmetric Synthesis of Silicon‐Stereogenic 5,10‐Dihydrophenazasilines via Enantioselective 1,5‐Palladium Migration

Abstract: A palladium-catalyzed asymmetric synthesis of silicon-stereogenic 5,10-dihydrophenazasilines was developed that proceeds via an unprecedented enantioselective 1,5-palladium migration. High enantioselectivity was achieved by employing 4,4'-bis(trimethylsilyl) (R)-Binap as the chiral ligand, and a series of mechanistic investigations were carried out to probe the catalytic cycle of this process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
28
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 96 publications
(29 citation statements)
references
References 97 publications
(7 reference statements)
1
28
0
Order By: Relevance
“…Suffert and co‐workers found the first catalytic 1,5‐palladium migration in Stille coupling (Scheme a) . In 2017, Nozaki described a palladium‐catalyzed intramolecular C(sp 2 )−H cyclization involving a 1,5‐palladium migration (Scheme b) . Apparently, extension of this 1,5‐palladium migration process to the remote functionalization of specific C(sp 3 )−H bonds is not only mechanistically interesting but also would significantly increase the utility of the process.…”
Section: Methodsmentioning
confidence: 97%
“…Suffert and co‐workers found the first catalytic 1,5‐palladium migration in Stille coupling (Scheme a) . In 2017, Nozaki described a palladium‐catalyzed intramolecular C(sp 2 )−H cyclization involving a 1,5‐palladium migration (Scheme b) . Apparently, extension of this 1,5‐palladium migration process to the remote functionalization of specific C(sp 3 )−H bonds is not only mechanistically interesting but also would significantly increase the utility of the process.…”
Section: Methodsmentioning
confidence: 97%
“…Undoubtedly, it is recognized as a challenge in the field of C−H activation to develop highly enantioselective catalytic methods toward chiral silanes because trigonal silicon is too unstable for synthetic transformations and many C−H activation reactions require harsh conditions. In fact, only intramolecular C−H bond functionalization approaches have been reported to access cyclic silicon‐stereogenic silanes such as dibenzosiloles and 5,10‐dihydrophenazasiline, including the direct arylation, dehydrogenative silylation, 1,5‐palladium migration reaction, and ring expansion/dehydrogenative silylation reactions. The pioneering work by the group of Gevorgyan showed that pyridine and pyrimidine serve as powerful directing groups in various C−H functionalization reactions of silicon‐tethered arenes (Scheme ).…”
Section: Methodsmentioning
confidence: 99%
“…However, some problems still remain in terms of the functional group tolerance and versatility of these previously reported synthetic methods due to the use of a stoichiometric amount of the organolithium reagents. In addition, despite these contributions, catalytic reaction systems have not been developed as much [26,27].…”
Section: Introductionmentioning
confidence: 99%